The Research and Desige of the CNC Constant Voltage Power - Shiwei Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
CNC constant voltage power is composed by the analog power circuit, MCU control circuit , pulse width modulation circuit, a power driver amplifier , analog to digital conversion circuit , the input voltage setting circuit and the output voltage display circuit. The power possesses the functions of digital regulator, high precision output, short-circuit & over-current protection and alarm functions, especially for a higher accuracy requirements for various occasions. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5443